Consistency in Geometry Among Coronary Atherosclerotic Plaques Extracted From Computed Tomography Angiography - Liu, Haipeng; Wingert, Aleksandra; Wang, Xinhong; Zhang, Jucheng; Sun, Jianzhong; Chen, Fei; Khalid, Syed Ghufran; Gong, Yinglan; Xia, Ling; Jiang, Jun; Wang, Jian'an; Zheng, Dingchang (Frontiers in Physiology, 2021)
Background: The three-dimensional (3D) geometry of coronary atherosclerotic plaques is associated with plaque growth and the occurrence of coronary artery disease. However, there is a lack of studies on the 3D geometric properties of coronary plaques. We aim to investigate if coronary plaques of different sizes are consistent in geometric properties. Methods: 19 cases with symptomatic stenosis caused by atherosclerotic plaques in the left coronary artery were included. Based on attenuation values on computed tomography angiography images, coronary atherosclerotic plaques and calcifications were identified, 3D reconstructed, and manually revised. Multidimensional geometric parameters were measured on the 3D models of plaques and calcifications. Linear and non-linear (i.e., power function) fittings were used to investigate the relationship between multidimensional geometric parameters (length, surface area, volume, etc.). Pearson correlation coefficient (r), R-squared and p-values were used to evaluate the significance of the relationship. The analysis was performed based on cases and plaques, respectively. Significant linear relationship was defined as R-squared>0.25 and p<0.05. Results: In total, 49 atherosclerotic plaques and 56 calcifications were extracted. In the case-based analysis, significant linear relationships were found between number of plaques and number of calcifications (r=0.650, p=0.003) as well as total volume of plaques (r=0.538, p=0.018), between number of calcifications and total volume of plaques (r=0.703, p=0.001) as well as total volume of calcification (r=0.646, p=0.003), and between the total volumes of plaques and calcifications (r=0.872, p<0.001). In plaque-based analysis, power function showed higher R-squared values than linear function in fitting the relationships of multidimensional geometric parameters. Two presumptions of plaque geometry in different growth stages were proposed with simplified geometric models developed. In the proposed models, the exponents in the power functions of geometric parameters were in accordance with the fitted values. Conclusion: In CAD patients, coronary plaques and calcifications are positively related in number and volume. Different coronary plaques are consistent in the relationship between geometry parameters in different dimensions.